Pain perception in female adolescents with borderline personality disorder - Ludäscher, Petra; Kalckreuth, Clemens Martin von; Parzer, Peter; Kaess, Michael; Resch, Franz; Bohus, Martin; Schmahl, Christian; Brunner, Romuald (European child & adolescent psychiatry, 2015)
Borderline personality disorder (BPD) is a severe and often debilitating psychiatric disorder that begins during adolescence. Core features of BPD are affective dysregulation, dysfunctional self-concepts, and difficulties in social interactive domains. A widely accepted marker for severe emotion dysregulation in adult BPD is decreased pain sensitivity. Until now it is unclear whether this characteristic feature of BPD is already present during adolescence. Thus, this study aims to investigate pain sensitivity in adolescent patients meeting DSM-IV criteria for BPD. 20 female adolescent patients with BPD (mean age 16.4 years) and 20 healthy age-matched control participants were investigated. Detection and pain thresholds for thermal stimuli were assessed on both hands. Furthermore, self-rating instruments were used to assess overall psychopathology, dissociation, and depression. We found significantly higher pain thresholds in patients with BPD than in healthy controls. Patients with BPD had higher intensities of depression, overall psychopathology, and dissociative symptoms, but there was no correlation between pain sensitivity and any of these measures of psychopathology. These findings are in line with previous findings in adult BPD patients concerning lower pain sensitivity as compared to healthy controls. This provides support for the idea that disturbed pain processing is not only a consequence of chronic BPD but is already present in early stages of BPD.